If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 = 0.6(9y + -15) Reorder the terms: 14 = 0.6(-15 + 9y) 14 = (-15 * 0.6 + 9y * 0.6) 14 = (-9 + 5.4y) Solving 14 = -9 + 5.4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5.4y' to each side of the equation. 14 + -5.4y = -9 + 5.4y + -5.4y Combine like terms: 5.4y + -5.4y = 0.0 14 + -5.4y = -9 + 0.0 14 + -5.4y = -9 Add '-14' to each side of the equation. 14 + -14 + -5.4y = -9 + -14 Combine like terms: 14 + -14 = 0 0 + -5.4y = -9 + -14 -5.4y = -9 + -14 Combine like terms: -9 + -14 = -23 -5.4y = -23 Divide each side by '-5.4'. y = 4.259259259 Simplifying y = 4.259259259
| 10c=260 | | 3(2a-6)=34 | | 9h=207 | | 34(19-5.5x)=16(5x-8)+53.1 | | 7g=91 | | 32=.5x(x+12) | | 7p=56 | | -1+-10= | | -3.45-1.5c=6.1(c+2.3) | | 0.3a-1.2=0.5a | | 36=.5x(x-5) | | f+20=61 | | 14a-10=19(a-3) | | 2.8x+65=5.3x+10 | | 8x+5y = 6 | | 3n-8=37+8n | | 7x-7=3x+9 | | e+49=61 | | 26-2(5+6)= | | x-6+2=4 | | 1.7m+7.28=-9.04 | | 8z-5=-11+5z | | d+13=35 | | e-27=19 | | 2x^2-40x=0 | | b+14=33 | | 4y^2+31y-8=0 | | d-41=34 | | 14(x-2)-4=12x+2 | | 3(-2u^2+5)= | | y^3-6y^2+8y=0 | | 8x+4(x-3)=4(6x+4)-4 |